DRUG DESIGN OF MEDICINAL PLANTS AS A TREATMENT OF OMICRON VARIANT (COVID-19 VARIANT B.1.1.529) - Mollaamin, Fatemeh (Journal of the Chilean Chemical Society, 2022)
The goal of this paper was determining the physical and chemical properties of some medicinal plants which are used against the Omicron Variant (Covid-19 variant B.1.1.529) symptoms. In this work, seven medicinal species for the most frequently symptoms of Omicron disease such as fever, cough, sore throat, shortness of breath, anorexia, muscle-joint pain, headache and Nausea-vomiting based on the fidelity level index has been accomplished. Positive stranded RNA viruses, coronaviruses (CoVs), can infect humans and multiple species of animals through enteric, respiratory, and central nervous system diseases with attractive targets for designing anti- Omicron conjunction. In this work, it has been investigated the compounds of thymol, gingerol, salvinorina A, cynnamil, curcumin, pulegone and rosmarinic acid as a probable anti pandemic Omicron receptor derived from medicinal plants and herbs of thyme, ginger , salvia divinorum, cinnamon leaves, curcuma longa (turmeric) , mentha pulegium (pennyroyal) and rosemary, respectively. Anti-Omicron through the hydrogen bonding using the physicochemical properties including heat of formation, Gibbs free energy, electronic energy, charge distribution of active parts in the hydrogen bonding, NMR estimation of medicinal ingredients jointed to the database amino acids fragment of Tyr-Met-His as the selective zone of the Omicron, positive frequency and intensity of different normal modes of these structures have been evaluated. The theoretical calculations were done at various levels of theory to gain the more accurate equilibrium geometrical results, and IR spectral data for each of the complex proposed drugs of N-terminal or O-terminal auto-cleavage substrate were individually determined to elucidate the structural flexibility and substrate binding of seven medicinal plants jointed to active site of Omicron molecule. A comparison of these structures with two configurations provides new insights for the design of substrate-based anti-targeting Omicron. This indicates a feasible model for designing wide-spectrum of anti- Omicron drugs. The structure-based optimization of these structures has yielded two more efficacious lead compounds, N and O atoms through forming the hydrogen bonding (H-bonding) with potent anti- Omicron Variant (Covid-19 variant B.1.1.529) .